2010
DOI: 10.5713/ajas.2010.80423
|View full text |Cite
|
Sign up to set email alerts
|

Imprinted Gene mRNA Expression during Porcine Peri-implantation Development

Abstract: Imprinted genes are essential for fetal development, growth regulation, and postnatal behavior. However, little is known about imprinted genes in livestock. We hypothesized that certain putatively imprinted genes affected normal peri-implantation development such as embryo elongation, initial placental development, and preparation of implantation. The objective of the present study was to investigate the mRNA expression patterns of several putatively imprinted genes during the porcine peri-implantation stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…On the other hand, both IGF-2 and IGF-2R are imprinted genes in pigs. IGF-2 has been reported to be paternally expressed, while IGF-2R is maternally expressed ( Nezer et al, 1999 ; Killian et al, 2001 ; Bischoff et al, 2009 ; Cha et al, 2010 ). If a gene is imprinted, the relative allelic expression activity and even individual phenotype may be different in progeny of reciprocal crosses ( Chaillet 1994 ; Curley and Keverne, 2004 ; Wittkopp et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, both IGF-2 and IGF-2R are imprinted genes in pigs. IGF-2 has been reported to be paternally expressed, while IGF-2R is maternally expressed ( Nezer et al, 1999 ; Killian et al, 2001 ; Bischoff et al, 2009 ; Cha et al, 2010 ). If a gene is imprinted, the relative allelic expression activity and even individual phenotype may be different in progeny of reciprocal crosses ( Chaillet 1994 ; Curley and Keverne, 2004 ; Wittkopp et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the IGF-2R gene is paternally imprinted in rodents, artiodactyls and marsupials, but is biallelically expressed in primates ( Killian et al, 2000 ). In pigs, it has been shown that IGF-2R is maternally expressed ( Killian et al, 2001 ; Bischoff et al, 2009 ; Cha et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%